Associations between contraception and stunting in Guatemala: secondary analysis of the 2014–2015 Demographic and Health Survey. Issue 1 (22nd August 2019) - Flood, David; Petersen, Ashley; Martinez, Boris; Chary, Anita; Austad, Kirsten; Rohloff, Peter
Abstract : Background: There has been limited research on the relationship between contraception and child growth in low-income and middle-income countries (LMICs). This study examines the association between contraception and child linear growth in Guatemala, an LMIC with a very high prevalence of child stunting. We hypothesise that contraceptive use is associated with better child linear growth and less stunting in Guatemala. Methods: Using representative national data on 12 440 children 0–59 months of age from the 2014–2015 Demographic and Health Survey in Guatemala, we constructed multivariable linear and Poisson regression models to assess whether child linear growth and stunting were associated with contraception variables. All models were adjusted for a comprehensive set of prespecified confounding variables. Results: Contraceptive use was generally associated with modest, statistically significant greater height-for-age z-score. Current use of a modern method for at least 15 months was associated with a prevalence ratio of stunting of 0.87 (95% CI 0.81 to 0.94; p<0.001), and prior use of a modern method was associated with a prevalence ratio of stunting of 0.93 (95% CI 0.87 to 0.98; p<0.05). The severe stunting models found generally similar associations with modern contraceptive use as the stunting models. There was no significant association between use of a modern method for less than 15 months and the prevalence ratio of stunting or severe stunting. Conclusions: Contraceptive use was associated with better child linear growth and less child stunting in Guatemala. In addition to the human rights imperative to expand contraceptive access and choice, family planning merits further study as a strategy to improve child growth in Guatemala and other countries with high prevalence of stunting.